2012
DOI: 10.1055/s-0032-1323677
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Augmentation with Non-Antidepressants over Sticking to Antidepressants after Treatment Failure in Depression: A Naturalistic Study

Abstract: Introduction: Non-response to an antidepressant monotherapy in unipolar depression is quite common. Therefore strategies for subsequent treatment steps are necessary. However, there is a lack of direct comparisons of these different strategies. In this naturalistic study we compared the outcome to different strategies after failure of the primary antidepressant treatment. Methods: Failure of primary antidepressant monotherapy occurred in 135 patients. 98 of these patients have been administered 4 treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…However, the small sample size (total n=98) is an important limitation of this study. 28 In line with the findings by Köhler et al, 28 a recent Korean naturalistic study 55 also found that patients have chosen AA therapy more than antidepressant combination and switching therapies when experiencing nonresponse to initial antidepressant treatment. In addition, AA therapy was shown to have more clinical benefit than antidepressant combination and switching.…”
Section: Which Strategy Is More Beneficial For Treating Patients Withsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the small sample size (total n=98) is an important limitation of this study. 28 In line with the findings by Köhler et al, 28 a recent Korean naturalistic study 55 also found that patients have chosen AA therapy more than antidepressant combination and switching therapies when experiencing nonresponse to initial antidepressant treatment. In addition, AA therapy was shown to have more clinical benefit than antidepressant combination and switching.…”
Section: Which Strategy Is More Beneficial For Treating Patients Withsupporting
confidence: 58%
“… 27 Anecdotal data support the usefulness of switching or combining antidepressant strategies; however, few clinical trials of such therapies have been conducted and the results are inconsistent. 18 28 29 30 31 32 A number of small RCTs have investigated the efficacy of switching therapy for depression (10 RCTs and 30 open-label studies). 27 33 34 35 According to these controlled clinical trials, the remission rates after switching therapy ranged from 10% to 80%.…”
Section: Which Strategies Are Popular As a Subsequent Treatment Optiomentioning
confidence: 99%
See 1 more Smart Citation
“…Only 74% of patients reached the study endpoint. These aspects are significantly different from other depression trials, such as the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) trial,2 and limit the generalisability of the results. Of note, augmentation with antipsychotics might increase the risk of some undesired but clinically significant side effects, for example, on metabolic or motor function, as also indicated by this study.…”
Section: Commentarymentioning
confidence: 85%
“…Even after several treatment approaches, the rate of patients with refractory depression is still 30% 1. In case of non-response to therapy, adding a drug from a different pharmaceutical class to the antidepressant treatment has been shown to have an augmentative effect 2. Most evidence is available for augmentation with lithium3 and atypical antipsychotics 4.…”
Section: Contextmentioning
confidence: 99%